Los pánicos morales en torno al mercado del sexo: Reflexiones en torno al discurso abolicionista de las organizaciones antitrata de la Provincia de Córdoba - Allione Riba, Guadalupe (Universidad Nacional de Villa María, 2019)
In this work we will analyze the representations around commercial sex that are present in the abolitionist discourse of Córdoba Province’s anti-trafficking organizations –the Sub-secretary of Assistance and Human Trafficking, the María de los Ángeles Foundation and the Civil Association “Vínculos en Red”-. Through interviews to the professionals that work in them, we will try to give an account on how this organizations reproduce moral and sexual panics regarding the sex market. We will reflect on how this is an operation that sustains itself on a specific conceptualization of prostitution: as exploitation, sexual violence and paid rape, linked directly and indisputably with sex trafficking. Finally, we will delve into the material effects that these type of sexual panics have over the lives of people that practice commercial sex, particularly the repressive and punitive consequences of abolitionism.